Serum and plasma myeloperoxidase in acute coronary syndrome and chronic stable angina - Hoe, Ng Wai (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Myeloperoxidase (MPO) plays essential roles in the pathogenesis of coronary plaque destabilization. This case-control study aimed to investigate the differences in EDTAplasma MPO level in acute coronary syndrome (ACS) and chronic stable angina (CSA). This study also aimed to investigate the differences in the MPO levels in serum and EDTAplasma samples among ACS and CSA patients. Cases involved 9 ACS patients (age 52.8±11.9 years; mean±S.D.) who underwent primary angioplasty, while 9 CSA patients (age 58.3±11.4 years; mean±S.D.) were recruited as controls. The MPO was measured in EDT A-plasma and matched serum samples collected from femoral artery, antecubital vein and at the culprit coronary artery using in-house developed and validated sandwich ELISA. C-reactive protein (CRP) served as reference protein. Serum MPO level was significantly higher compared to EDTA-plasma in ACS and CSA. For ACS, the MPO level (mean±SD) in serum was significantly higher in venous blood (2864.64±1777.40 ng/ml vs. 1321.31±319 .02 ng/ml, p=0.021) and intracoronary blood (2949 .31±2170.21 ng/ml vs. 1230.08±383.85 ng/ml, p=0.033) compared to EDTA-plasma. However, there was no significant difference (p=0.171) between serum and EDTA-plasma MPO level for blood taken from femoral artery. For CSA, there were significant differences between serum and EDTA-plasma MPO level in femoral arterial blood (2521.29±1266.97 ng/ml vs. 549 .65±526.09 ng/ml, p=0.001 ), antecubital venous blood (2171.25±983 .27 ng/ml vs. 725.27±671.56 ng/ml, p=0.004) and intracoronary arterial blood (1979.59±912.41 ng/ml vs. 621.00±528.93 ng/ml, p=0.001). The EDTA-plasma MPO concentration was significantly higher in ACS compared to CSA for blood sampled from femoral artery (1259.19±405.49 ng/ml vs. 549.65±526.09 ng/ml, p=0.005), antecubital vein (1321.31±319.02 ng/ml vs. 725.27±671.56 ng/ml, p=0.031) and intracoronary artery (1321.31±319.02 ng/ml vs. 725.27±671.56 ng/ml, p=0.013). There was however no significant association between MPO and CRP concentration in ACS and CSA. These findings suggest that MPO concentration in EDTA-plasma were dissonant with those measured in matched serum samples. The EDT A-plasma is the preferred specimen for MPO measurement as its value is not confounded by poorly controllable ex vivo release of MPO from leucocytes as in serum. This study also shows that EDT A-plasma MPO is significantly higher in patients with ACS compared with CSA patients. These findings suggest a potential role of MPO as a marker of atheromatous plaque growth and wlnerability. Large cohort studies are required to establish the clinical importance and pathogenic significance of MPO in plaque destabilization.